Design of Selective Plasmodium falciparum Kinase Inhibitors using Computer-Aided Drug Discovery - Kamunya, Stephanie Gathoni (Department of Chemistry, 2023)
The discovery of antimalarials with novel mechanisms of action able to circumvent resistance is crucial. This target-based drug discovery campaign is based on the following Plasmodium kinases: Plasmodium falciparum phosphatidylinositol 4-kinase (PfPI4K) and Plasmodium falciparum cyclic guanosine monophosphate (cGMP)-dependent Protein Kinase (PfPKG). The aim of this study was to use computer-aided drug design (CADD) methods to rationally design and accelerate the identification of P. falciparum kinase inhibitors. The foremost part of this project was focused on the design and synthesis of novel analogues of the anticancer human mammalian target of rapamycin (mTOR) inhibitor MLN0128 as dual PfPI4K/PfPKG inhibitors. Using structure-based drug design methods, several strategies were used to design potent dual PfPI4K/PfPKG inhibitors with reduced activity against human kinases specifically mTOR and human type III beta phosphatidylinositol-4 kinase (HuPI4KIIIβ). Selected compounds were prioritized for synthesis and were screened against the whole-cell parasite and the respective kinases: Plasmodium PI4K and PKG. Compound 46h demonstrated high PvPI4K potency with an IC50 of 0.002 nM. The most potent PfPKG inhibitors, 46b (0.12 µM) and 46g (0.18 µM) also exhibited relatively good whole-cell activity with PfNF54 IC50 values of 0.66 µM and 0.4 µM, respectively. High selectivity was also maintained relative to the human ortholog, HuPI4KIIIβ, and moderate selectivity was achieved relative to the mTOR kinase. MMV652103, an imidazopyridazine lead compound showed potent inhibition of PvPI4K (PvPI4K IC50: 0.0008 µM) but moderate PfPKG inhibition with a PfPKG IC50 of 0.12 µM. Therefore, the second part of this project was focused on optimising PfPKG inhibition by compounds belong to this chemotype. Using chemoinformatic approaches, compounds from an in-house imidazopyridazine library were prioritised for PfPKG inhibition assays to validate molecular docking findings and understand protein-inhibitor interactions important for PfPKG inhibition. These findings were then used to select more compounds from the in-house library for PfPKG screening which demonstrated IC50 results ranging from 0.007 to >30 µM. These data, coupled with molecular docking and molecular dynamics studies, provided valuable insight into structural features driving PfPKG inhibition. The final part of this project was to virtually screen the Pandemic Response Box (PRB) for potential PfPI4K and/or PfPKG inhibitors. Of the 400 compounds in the PRB, 21 were selected for enzymatic screening after virtual screening using the PvPKG crystal structure and the PfPI4K homology model. Four hits were identified against PfPKG (approximately 20% success rate) and two against PvPI4K (approximately 10% success rate). Hence, the novel chemotypes (1H-pyrrolo[2,3-b]pyridine and pyrimidine-2,4-diamine) may be optimized for increased dual PfPKG/PvPI4K inhibition potency. In summary, using CADD methods, this project identified analogues of various chemotypes as PfPI4K and PfPKG inhibitors.